Determinants of small-scale irrigation adoption in drought-prone areas of northcentral Ethiopia in the context of climate change - Asfaw Eshetu, Amogne; Mekonen, Abebe Arega (Frontiers in Climate, 2024)
IntroductionOne feasible way to prepare for the adverse effects of climate change in rainfed-dependent livelihood zones is through irrigation. This study examines small-scale irrigation practices and their determinants.MethodsUsing structured survey questionnaires, interviews, and field observations, we used a cross-sectional survey design to collect data from 380 randomly selected households. The data analysis involved percentages, problem confrontation index, Chi-square test, independent samples t-test, and binary logistic regression model.ResultsThe findings revealed that river/stream diversion (40%), using nearby springs (19%), and hand-dug walls (18%) were the predominant types of irrigation. At the same time, water scarcity (PCI = 743), land shortage (PCI = 345), and labor (PCI = 212) were the main impediments to irrigation practices. The binary logistic regression model revealed educational status (OR = 1.239, p < 0.05), headship type (OR = 0.246, p < 0.05), age (OR = 0.943, p < 0.05), relative agroecological location (OR = 7.605; 13.929, p < 0.05), family size (OR = 1.936, p < 0.05), land size (OR = 8.609, p < 0.05), responsibility (OR = 2.069, p < 0.05), and crop failure (OR = 0.389, p < 0.05) as factors affecting the adoption of small-scale irrigation.DiscussionWe recommend offering financial assistance to farmers with limited resources to acquire and install labor- and water-saving irrigation systems. Training and extension services on operating and maintaining small-scale irrigation technologies should be provided. Timely information sharing is also necessary to increase the use of irrigation on a small scale as a feasible adaptation to climate change.